Stanley ole Neboo's Zoom meeting transcript on Kenya, January 31, 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
To have access to the research data file, please contact: Joana Roque de Pinho: roquedepinho.joana@gmail.com
Keywords: Arid regions; Maasai (African people); Livestock; Vaccination; Tourism; Prices; Travel; Pastoralist; Conservancy; Lockdown; Sociality; Ghana; Kenya; Tanzania; Senegal; Mobility; COVID-19 Pandemic